Theoretization of the possibilities of the use of scientific quotation and scientific search in providing the quality of scientific research - A. B. Yuriev; A. R. Fastykovsky; O. A. Kozyreva (Вестник Северо-Кавказского федерального университета, 2023)
The article describes the possibilities of improving the quality of using scientific citation and scientific search in the system of continuous education. The integrity of the formulation of the problem of the development of students and teachers is highlighted in the context of the ideas and technologies of lifelong education, in the structure of which work is carried out on diploma theses (SVE), final qualification works (HE), final attestation works (FPE) and the realized form is determined in theorization and implementation of ideas. protection. The possibilities of using various types of scientific citation in the system of continuous education are identified and substantiated, the models of scientific search in the structure of performing scientific work in pedagogy are described, and the foundations of the adaptive-productive inclusion of a student in the system of research work in pedagogy are disclosed. The principles of using scientific citation and scientific search in ensuring the quality of scientific research in pedagogy are determined and illustrated. The possibilities of using didactic and scientific theorizing in the professional development of a teacher are compared. The pedagogical conditions for increasing the effectiveness of the use of scientific citation and scientific search in ensuring the quality of scientific research in pedagogy are characterized. The directions of future scientific publications in the structure of the description and study of the theorized process are highlighted.